2022
DOI: 10.1021/acsomega.2c05184
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Study on the Reinforcement of Electrospun PHB Scaffolds with Composite Magnetic Fe3O4–rGO Fillers: Structure, Physico-Mechanical Properties, and Piezoelectric Response

Abstract: This is a comprehensive study on the reinforcement of electrospun poly(3-hydroxybutyrate) (PHB) scaffolds with a composite filler of magnetite–reduced graphene oxide (Fe3O4–rGO). The composite filler promoted the increase of average fiber diameters and decrease of the degree of crystallinity of hybrid scaffolds. The decrease in the fiber diameter enhanced the ductility and mechanical strength of scaffolds. The surface electric potential of PHB/Fe3O4–rGO composite scaffolds significantly increased with increasi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 90 publications
0
2
0
Order By: Relevance
“…The increase in the H c of all composite scaffolds is associated with a low content of magnetite particles. The particles cease to interact magnetostatically with each other; as a result, magnetite chain aggregates disrupt in the composite [ 53 ]. The value of H c facilitates a distribution of magnetic nanoparticles in the polymer fibers.…”
Section: Resultsmentioning
confidence: 99%
“…The increase in the H c of all composite scaffolds is associated with a low content of magnetite particles. The particles cease to interact magnetostatically with each other; as a result, magnetite chain aggregates disrupt in the composite [ 53 ]. The value of H c facilitates a distribution of magnetic nanoparticles in the polymer fibers.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, it has been found that the crystallinity of an electrospun polymer directly correlates with the fiber diameter [ 73 , 74 ]. The latter can be adjusted by varying the parameters of electrospinning [ 63 ]; accordingly, crystallinity and consequently piezoelectricity also strongly depend on the electrospinning process.…”
Section: Requirements For the Design Of Piezoelectric Nerve Scaffoldsmentioning
confidence: 99%